PENGARUH TINGKAT HUTANG, ARUS KAS OPERASI, PENGHINDARAN PAJAK DAN LIKUIDITAS TERHADAP PERSISTENSI LABA: Studi Empiris pada Perusahaan Sektor Barang dan Konsumsi Subsektor Farmasi yang Terdaftar di Bursa Efek Indonesia - Octania Denita; Mohamad Safii (LPPM Universitas Bina Bangsa, 2022)
This study aims to determine the effect of debt levels, operating cash flow, tax avoidance and liquidity on earnings persistence (empirical study of pharmaceutical sub-sector consumer goods industry companies listed on the Indonesia Stock Exchange for the 2015-2020 period). This type of research is a quantitative approach research with descriptive analysis method. Samples were taken using purposive sampling technique. The sample consists of 60 data from 10 companies in the consumer goods industry in the pharmaceutical sub-sector listed on the Indonesia Stock Exchange in 2015-2020. The data analysis technique used is descriptive statistical technique and panel data regression using Eviews 12. Based on the results of this study, it shows that leverage, operating cash flows, tax avoidance and liquidity have a simultaneous effect on earnings persistence. Operating cash flow has influence on earnings persistence, leverage, tax avoidance, and liquidity have no effect on earnings persistence